MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATERI LUAS DAN KELILING BANGUN DATAR KELAS IV SEKOLAH DASAR - Handayani, Tutwuri (Jurnal Pembelajaran Prospektif, 2021)
The implementation of the 2013 curriculum (K-13) has a consequence that teachers must be more qualified in carrying out learning activities. Because K-13 mandates the application of a scientific approach (5M) which includes observing, asking, gathering information, reasoning / associating, and communicating. Mathematic Teachers North Bintan Elementary School often did not give opportunity for students to get the opportunity to think creatively, critically,collaboratively and communicatively. This happens because the learning model carried out by the teacher has not implemented a learning model that can optimally accommodate students' interests and potential. Researchers have taught as classroom teachers since 2012. In the 2018/2019 academic year, researchers taught fourth grade. As a class teacher, the writer teaches all subjects, including PPKN, Indonesian, Mathematics, Science, Social Studies, andSBdP. Of the six subjects, the lowest average score for daily tests was mathematics. Basic mathematics competencies are in semester II include KD 3.9, namely; Explaining and determining the perimeter and area of squares, rectangles, and triangles as well as the square relationship with the square root is the KD with the lowest score for the daily test scores of grade IV a SD Negeri 003 Bintan Utara. Class IV mathematics learning process at SD Negeri003 North Bintan often did not make students get the opportunity to think creatively, critically, collaboratively and communicatively, this happened because the learning model carried out by the teacher has not implemented a learning model that could optimally accommodate students' interests and potential. The impact was that many students could not achieve the minimum mastery level at 72. The purpose of writing this paper was to describe mathematics learning atSD Negeri 003 North Bintan, and to describe the Learning Implementation Plan with the Discovery Learning learning model, and to describe the Discovery Learning scenario. The basis for this paper was the low level of understanding of students in doing math problems.